Aktivitas Ekstrak Meniran (Phyllanthus niruri linn) Sebagai Immunostimulator pada Ayam yang Divaksin Penyakit Tetelo - Rahmahani, Jola; Ernawati, Rahaju; Handijatno, Didik (Jurnal Veteriner; Vol 22 No 1 (2021), 2021)
Newcastle Disease or tetelo is one of main problem in poultry Industry in Indonesia. Prevention such as biosecurity control and routin vaccination program have been conducted to overcome this problem, but they have not given any great impact. Phyllanthus Niruri L. or meniran is well known as immunostimulatory. This research was aimed to reveal effect of Phyllanthus Niruri L. extract on chicken vaccinated with live vaccine LaSota. Administration of Phyllanthus Niruri L. extract was conducted on three different time which were 7 days before vaccination, 1 days after vaccination, and 3 days before and after vaccination. The amount of Phyllanthus Niruri L. extract administered were 2 ml, 2.5 ml, and 3 ml orally. Data of antibody titre were collected for 4 weeks after the treatment. It was obtained by measuring the antibody through Haemagglutination Inhibition test each week. According to the result Phyllanthus Niruri L. extract could increase the amount of antibody titre against Newcastle Disease. The amount of Phyllanthus Niruri L. extract given that capable to induced maximum of antibody titre was administered 1 days after the vaccination with  amount 2.5 ml. It is suggested that Phyllanthus Niruri L. extract should be administered post vaccination to boost antibody synthesis.